The Effectiveness of Problem Based Learning (PBL) Based Socioscientific Issue (SSI) to Improve Critical Thinking Skills - Muflichatu Nur Fita; Budi Jatmiko; Elok Sudibyo (Studies in Learning and Teaching, 2021)
The purpose of this research was to see how effective the Problem Based Learning (PBL) based Socioscientific Issues (SSI) is at improving critical thinking skills. The sample used was grade seven in SMPN 4 Lamongan with 2 classes and each class contains 15 students. The design of the learning materials trial used One-Group pre-test post-test design. Tests of critical thinking skills and student answer sheets were used to collect data. Techniques of data analysis used N-gain, paired t-test, and independent t-test. The result of this research is as follows: The effectiveness in terms of the critical thinking skills test the category increase is high, there is a significant difference between the test before and after learning with PBL based SSI and there is no difference N-gain in the two group classes and students' responses are classified as very good. Based on data analysis, it can be concluded that PBL with SSI is effective to improve critical thinking skills. The implications of this study are PBL-based SSI has the potential to be an innovative solution and alternative for improving critical thinking skills.